2019
DOI: 10.3390/ph12010018
|View full text |Cite
|
Sign up to set email alerts
|

[177Lu]Lu-PSMA-617 Salivary Gland Uptake Characterized by Quantitative In Vitro Autoradiography

Abstract: Irradiation of salivary glands remains the main dose-limiting side effect of therapeutic PSMA-inhibitors, especially when using alpha emitters. Thus, further advances in radiopharmaceutical design and therapy strategies are needed to reduce salivary gland uptake, thereby allowing the administration of higher doses and potentially resulting in improved response rates and better tumor control. As the uptake mechanism remains unknown, this work investigates the salivary gland uptake of [177Lu]Lu-PSMA-617 by autor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 28 publications
6
40
0
Order By: Relevance
“…One possible explanation is that there could be both PSMA receptor-speci c and non-speci c components (such as passive diffusion) to the observed salivary [ 18 F]DCFPyL accumulation, and the DCFPyL was only able to block the receptor-speci c component. Our ndings seem to agree with prior published data using pig SG autoradiography of [ 177 Lu]Lu-PSMA-617 demonstrating both PSMA-speci c and non-speci c uptake in the SG [23].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…One possible explanation is that there could be both PSMA receptor-speci c and non-speci c components (such as passive diffusion) to the observed salivary [ 18 F]DCFPyL accumulation, and the DCFPyL was only able to block the receptor-speci c component. Our ndings seem to agree with prior published data using pig SG autoradiography of [ 177 Lu]Lu-PSMA-617 demonstrating both PSMA-speci c and non-speci c uptake in the SG [23].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, a recently published clinical study of 16 patients using both orally-ingested and topical MSG demonstrated that while SG uptake of 68 Ga-PSMA-11 can be reduced with this intervention, tumor uptake of 68 Ga-PSMA-11 also declined which makes this approach unlikely to be clinically useful in the setting of TRT [29]. Administration of precursor of PSMA inhibitor 2-(phosphonomethyl) pentanedioic acid (2-PMPA) before 177 Lu-PSMA-617 site-speci cally blocked the uptake of PSMA-TRT in the SGs and kidneys without affecting the accumulation of the agents in the tumor, but this approach also needs further studies to validate its effectiveness [30].…”
Section: Discussionmentioning
confidence: 99%
“…However, the exact proportion of each form of uptake is still uncertain, and the mechanism of the nonspecific uptake is still unclear [29][30][31][32]. Recently, it has been reported that the accumulation of PSMA-targeted radioligands in salivary gland tissue is mainly caused by nonspecific uptake [18,33]. Further research will be necessary to investigate the exact mechanism of radioligand accumulation in salivary glands.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the PSMA structures in murine kidneys and salivary glands have been reported to differ [117,118]. Finally, the high PSMA binding in the salivary gland in humans may not only be due to PSMA expression, but might also be the result of non-specific binding [119,120].…”
Section: Protection Of Psma Expressing Kidneys and Salivary Glandsmentioning
confidence: 99%